Peran Guru Pendidikan Agama Kristen dalam Pembentukan Karakter Siswa Kelas VIII SMP N 1 Atap Basmuti di Masa Pandemi Covid 19 - Amran Maher Dionizius Isu; Maglon Ferdinand Banamtuan; Yakup Lopo (Jurnal Pendidikan Agama Kristen (JUPAK), 2021)
The aim of this study is to describe the role of Christian religious education teachers in shaping the character of students at the Basmuti One Roof Junior High School during the covid 19 pandemic. This research is a qualitative research with a descriptive method. The subject of this research is the teacher of Christian religious education subject at Basmuti One Roof State Junior High School. This research can use three steps in data collection, namely: observation, structured interviews and documentation studies. So the results obtained from this study are the teacher's role in shaping the character of students at the Basmuti One Roof Junior High School, namely: 1). The teacher's role in the formation of student character, includes providing motivation, can facilitate, for example in setting an example and increasing student creativity. 2). Characters that are instilled in students are honesty, responsibility, increase student creativity, and cooperation.